HUBUNGAN SELF ESTEEM DAN ALTRUISME DENGAN MOTIVASI MENJADI RELAWAN BENCANA PADA MAHASISWA FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA - Ani Lestari (2022)
Indonesia is a country that has a high risk of disasters. Volunteers are important part of disaster management including the health workers. The lack of capacity of health workers in disaster areas can occur. To comply the role of health workers, health students are needed to participate as volunteers in disaster areas. This study aims to determine the correlation between self esteem and altruism with motivation to become disaster volunteers in students of the Faculty of Health Sciences UPN Veteran Jakarta. This study used a descriptive analytic method with cross sectional approach, by accidental sampling technique of 324 respondents, the data was processed use chi-square test. This study showed a significant correlation between self-esteem and motivation to become a disaster volunteer p=0,001 (OR) = 2,170 and a significant correlation between altruism and motivation to become a disaster volunteer p=0,000 (OR) = 5,201. The conclusion of this study is the higher of self esteem and altruism of a person, the higher the motivation to become a disaster volunteer. Hopes the health students as potential health workers in future can participate in disaster management then increase their motivation as a volunteer especially in disaster areas.